Effect of scheduling of drip irrigation on growth, yield and water use efficiency of turmeric (Curcuma longa L.) var. CO 2 - Chitra, R; Havaraddi, R M; Subramanian, S; Suresh, J (Journal of Spices and Aromatic Crops, 2017)
Field experiments were conducted during 2012–13 and 2013–14 at Horticulture College and Research Institute, Coimbatore (Tamil Nadu) on black clay loam soil to study the effect of scheduling of drip irrigation on the growth, yield and water use efficiency of turmeric (cv. CO 2). The experiment included two intervals and three levels of irrigation with surface irrigation as control. Significantly higher rhizome yield was recorded in one day interval of irrigation at 80% PE (T2) (42.79 t ha-1) which was on par with two days interval of irrigation at 80% PE (T3) (42.51 t ha-1). Significantly higher number of leaves, leaf area, number of tillers, plant height and dry matter production were recorded in T2 and T3 compared to flood irrigation. Both one day and two days interval of irrigation and 40% PE recorded significantly higher WUE. The intervals and levels of irrigation were significantly superior for WUE, compared to surface irrigation.